Molecular and genome size analyses of somaclonal variation in apple rootstocks Malling 7 and Malling 9 - Noormohammadi, Zahra; Fazeli, Shokoohef; Sheidai, Masoud; Farahani, Farah (Acta Biologica Szegediensis, 2015)
The cultivated apple (Malus domestica) is important fruit crops cultivated in world. For production and breeding of high quality apple, inducing and enhancing new genetic diversity and suitable traits are necessary. In Iran, different local and imported apple genotypes are cultivated and common apple root stocks (Malling 7) M7 and (Malling 9) M9 are mostly used root stocks in the country. Therefore, we studied genetic diversity of M7 an M9 tissue culture regenerated plants produced by different treatments by using twenty ISSR markers. In total 51 randomly selected plants were studied for the occurrence of somaclonal variation in apple mother plants and tissue culture regenerated plants. Four different treatments were used for tissue culture. Genetic diversity parameters, genetic distance and polymorphism percentage were studied in regenerated plants. Variations in loci frequency and combination were checked by STRUCTURE and the presence of similar loci in the plants was studied by reticulation NJ tree. Genetic relationship versus distinctness was determined by principal coordinate analysis. The results showed the occurrence of genetic variation among mother plants and tissue culture regenerated plants of each subculture due to somaclonal variation. Significant difference in the genome size among some of the regenerated plants indicates that change in genetic structure of plants during tissue culture is also accompanied with quantitative change in DNA. However, degree of genetic variation differed among apple rootstocks and also among different treatments used.